PENGARUH JOB RESOURCES TERHADAP WORK ENGAGEMENT MELALUI BURNOUT KARYAWAN INDUSTRI MANUFAKTUR DI SALATIGA - Mokhammad Khukaim Barkhowa (STIE Pelita Nusantara Semarang, 2020)
Work engagement affects several aspects of the company. Work engagement is the latest issue in managing human resources (HR). Work engagement is the latest issue in managing human resources (HR). Work engagement is defined as a positive and satisfying mental state related to work characterized by vigor, dedication, and absorption.One maximal work attitude in contributing as a predictor of institutional performance is engagement. The purpose of this study was to analyze the effect of job resources on work engagement through burnout as an intervening variable. The sample of this study was 100 respondents. Sampling using snowball sampling is a sampling technique that first starts with a small amount and then enlarges. Data analysis using multiple linear regression models, simple linear regression models and sobel tests. The results of hypothesis testing job resources positive affect the work engagement, burnout negative affect the work engagement, job resources negative effect on burnout, job resources affect the work engagement through burnout.